The Effect of Perceived Value and Brand Image on Customer Loyalty With Customer Satisfaction as Intervening Variable for Aerostreet Products - Zidan, Muhammad; Udayana, Ida Bagus Nyoman; Cahya, Agus Dwi (International Journal of Economics Development Research (IJEDR), 2024)
With customer satisfaction acting as a mediating variable, this study examines the impact of perceived value and brand image on customer loyalty with a focus on Aerostreet products in Klaten, Central Java. Data from 118 individuals were collected via a Google Forms questionnaire utilizing non-probability and purposive sampling techniques, and path analysis was used for analysis. The results show that brand image and perceived value are not directly related to customer pleasure or loyalty. However, consumer happiness is directly impacted by brand image, and customer loyalty is therefore affected by this relationship. These findings suggest that while perceived value and brand image might not cause loyalty directly, a strong brand image raises customer satisfaction, which in turn encourages loyalty.